Two Cases of Infected Aortic Abdominal Aneurysm with Spondylodiskitis - Tohyama, Satoshi; Koyanagi, Hitoshi; Maeda, Tomohiro; Tsukui, Hiroyuki; Aomi, Shigeyuki; Kunii, Yoshifumi; Nishinaka, Tomohiro (Japanese Journal of Cardiovascular Surgery, 1999)
We encountered two cases of infected aortic abdominal aneurysm with spondylodiskitis. Both cases were diagnosed on the basis of fever, back pain and pulsatile abdominal mass. A 69-year-old man, case 1, underwent in situ reconstruction 1 year from the onset, because the infection was controllable by antibiotics and he had diabetes mellitus. A 68-year-old man, case 2, underwent operation while his infection was still active, because of paralysis of the bilateral lower extremities, aggravated by invasion of the vertebrae by the abscess. To prevent artificial graft infection, he underwent axillo-femoral bypass, which was extra-anatomical reconstruction, after the infected aneurysm and vertebrae were removed during aortic clamping above the aneurysm and bilateral common iliac arteries. Each stump was sutured and anterior fixation of the vertebrae was performed using an iliac bone graft. The postoperative course of both patients was successful. These cases suggest that the timing and procedure of the operation for infected aortic abdominal aneurysm with spondylodiskitis should be decided depending on the activity of infection, complications, age and activity of daily life of patients.